Tractable epidemiological models for economic analysis - Martín Gonzalez-Eiras; Dirk Niepelt (Swiss National Bank, Study Center Gerzensee, 2020)
We contrast the canonical epidemiological SIR model due to Kermack and McKendrick (1927) with more tractable alternatives that offer similar degrees of "realism" and flexibility. We provide results connecting the different models which canbe exploited for calibration purposes. We use the expected spread of COVID-19 in the United States to exemplify our results.
Keywords: I18; 330; Epidemiology; SIR model; logistic model; Covid-19